Analysis of Community Participation And Satisfaction of Sports Open Space In The City of Makassar - Nurhikma Amal; Juhanis Juhanis; Muh. Adnan Hudain; Yasriuddin Yasriuddin; Muhammad Rachmat Kasmad (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
The purpose of the study was to determine the level of participation and community satisfaction with sports open space in Makassar. This type of descriptive research uses a survey analysis research design. The population is all visitors to sports open spaces in CPI, Pakui Sayang Park, Sudiang Gor and Macan Park with the number of samples used, namely 50 people with the sampling technique is a random system. The data analysis technique used is descriptive analysis, and categorization analysis through the SPSS 20.00 program at a significant level of 95% or α 0.05. The results showed that; (1) Analysis of the level of public participation in sports open space in Makassar City as follows; (a) The level of public participation in sports open space in CPI is in the Fasting category or 34%; (b) The level of public participation in sports open space in Pakui Sayang Park is in the Fasting category or 42%; (c) The level of public participation in sports open space in Gor Sudiang is in the Fasting category or 34%; (d) The level of community participation in sports open space at Macan Park is in the Less Fasting category or 32%; and (2) Analysis of the level of community satisfaction with sports open space in Makassar City as follows; (a) The level of community satisfaction with sports open space at CPI is in the Fasting category or 38%; (b) The level of public satisfaction with sports open space in Pakui Sayang Park is in the Fasting category or 36%; (c) The level of public satisfaction with sports open space in Gor Sudiang is in the Fasting category or 34%; and (d) The level of public satisfaction with sports open space in CPI is in the Less Fasting category or 36%. The conclusion of the level of public participation and satisfaction with sports open space in CPI is in the satisfied category, in Pakui Sayang Park is in the satisfied category, in Gor Sudiang is in the satisfied category, and Taman Macan is in the less satisfied category.